DEVELOPING UMKM BUSINESS THROUGH ACCOUNTING EDUCATION IN AN EFFORTS TO IMPROVE THE ECONOMY IN KADUDAMPIT VILLAGE, SUKABUMI REGENCY - Indupurnahayu, Indupurnahayu; Lysandra, Shanti; Catheryn, Catheryn; Sparta, Sparta; Ahalik, Ahalik (LPPM Univ. Ibn Khaldun Bogor, 2024)
The purpose of this community service activity is to contribute to Accounting education for MSMEs by implementing several stages, namely bookkeeping and calculating the cost of products that can improve skills in MSME businesses. The implementation of community service activities consists of several stages: The planning stage by conducting observations and preliminary interviews with prospective partners. The stage of carrying out activities in the form of accounting education. The monitoring stage carries out post-test activities which aim to see the problems being faced by MSMEs in preparing financial reports independently. This community service was carried out in Kadudampit village on June 29, 2024. Accounting education was attended by 31 business actors consisting of three villages, namely tourism MSMEs, processed food MSMEs, trade and agriculture MSMEs. The results of the community service evaluation showed that there had been an increase in knowledge in accounting records, although it was not optimal. The preparation of inadequate financial reports and the calculation of the cost of production that was not yet accurate would have an impact on determining the selling price. In this case, there still needs to be assistance until they can be independent in efforts to improve the economy with MSME business strategies in the Kadudampit village environment.